Expression of Gast, Cckbr, Reg1a genes in rat duodenal epithelial cells upon long-term gastric hypoacidity and after a multiprobiotic administration - Dranitsina, A.S.; Savko, U.V.; Dvorshchenko, K.O.; Ostapchenko, L.I. (Вiopolymers and Cell, 2014)
Aim. Determination of the Cckbr, Gast and Reg1a genes expression in rat duodenal epithelial cells upon long- term hypoacidity and with the administration of the multiprobiotic Symbiter. Methods. The experiments were carried out on white non-strain male rats. The hypoacidic state was induced through intraperitoneal injection of omeprazole for 28 days. The level of genes expression was determined by semi-quantitative analysis with RT-PCR Results. The elevation of mRNA levels of the Cckbr and Gast genes in rat duodenal villus and crypt epitheliocytes, the increased expression of the Reg1A gene in crypt epithelial cells were shown as well as the appearance of the Reg1a gene expression in villus epitheliocytes upon hypoacidic conditions were shown. The content of mRNAs of the above mentioned genes decreased or remained at the control level upon the treatment of hypoacidic rats with the multiprobiotic Symbiter. Conclusions. Long-term gastric hypoacidity is accompanied by the changes in expression of the Cckbr, Gast and Reg1a genes in rat duodenum, whereas upon administration of the multiprobiotic Symbiter the pattern of studied gene expression did not changed in the most cases. Мета. Дослідити експресію генів Cckbr, Gast і Reg1a у дванадцятипалій кишці щурів за умов тривалої гіпоацидності та за введен- ня мультипробіотика Симбітер. Методи. Досліди виконано на білих нелінійних щурах-самцях. Гіпоацидний стан моделювали інтраперитонеальним введенням омепразолу протягом 28 діб. Рівень експресії генів визначали напівкількісним аналізом результатів ЗТ-ПЛР. Результати. Показано зростання рівня мРНК генів Cckbr і Gast в епітеліоцитах ворсинок і крипт дванадцятипалої кишки щурів; підвищення рівня експресії гена Reg1a в епітеліоцитах крипт, а також появу експресії цього гена в епітеліальних клітинах ворсинок за гіпоацидного стану. При введенні мультипробіотика Симбітер за тих же умов вміст мРНК досліджуваних генів зменшувався або був на рівні контрольних значень. Висновки. Стан тривалої шлункової гіпоацидності супроводжується зміною експресії генів Cckbr, Gast і Reg1a у дванадцятипалій кишці щурів, тоді як за введення мультипробіотика Симбітер патерн експресії цих генів у більшості випадків подібний до контролю. Цель. Исследовать экспрессию генов Cckbr, Gast и Reg1a в эпителиоцитах двенадцатиперстной кишки крыс в условиях длительной гипоацидности, а также при введении мультипробиотика Симбитер. Методы. Исследования проведены на белых нелинейных крысах-самцах. Состояние гипоацидности желудка моделировали интраперитонеальным введением омепразола в течение 28 дней. Уровень экспрессии генов определяли полуколичественным анализом результатов ОТ-ПЦР. Результаты. Показано повышение уровня мРНК генов Cckbr и Gast в эпителиоцитах ворсинок и крипт двенадцатиперстной кишки крыс; увеличение уровня экспрессии гена Reg1a в эпителиоцитах крипт, а также появление экспрессии этого гена в эпителиальных клетках ворсинок при гипоацидности. При введении мультипробиотика Симбитер в тех же условиях содержание мРНК проанализированных генов уменьшалось или было на уровне контрольных значений. Выводы. Состояние длительной желудочной гипоацидности сопровождается изменением экспрессии генов Cckbr, Gast и Reg1a в двенадцатиперстной кишке, тогда как при введении мультипробиотика Симбитер паттерн экспрессии исследованных генов в большинстве случаев близок к контролю.